Butcher's Crossing [videorecording (DVD)] - Polsky, Gabe; Satre-Meloy, Liam; Cage, Nicolas, 1965-; Hechinger, Fred; Berkeley, Xander, 1955-; Keller, Rachel, 1991-; Bobb, Jeremy; Raci, Paul; Williams, John, 1922-1994 (Sony Pictures Home Entertainment, 2023)
Based on the seminal novel by John Edward Williams, Gabe Polsky's epic frontier adventure, Butcher's Crossing, is a riveting commentary on human nature, ambition, masculinity, and man's relationship to his natural environment. A gritty story about buffalo hunters in the Old West. Will Andrews has left Harvard to find adventure. He teams up with Miller, a mysterious frontiersman offering an unprecedented number of buffalo pelts in a secluded valley. Their crew must survive an arduous journey where the harsh elements will test everyone's resolve, leaving their sanity on a knife's edge.